Exploring the synergy of problem‐based learning and computational fluid dynamics in university fluid mechanics instruction - Mora‐Melia, Daniel; Gutiérrez‐Bahamondes, Jimmy H.; Iglesias‐Rey, Pedro L.; Martinez‐Solano, Francisco Javier (Computer applications in engineering education, 2024)
Recently, the growing demand for computational fluid dynamics (CFD) skills in industry has highlighted the importance of their incorporation into university academic programs at both the undergraduate and graduate levels. However, many academic programs treat CFD tools as a “black box” in which users simply enter data without fully understanding the inner workings of the software or its application in real‐world situations. Therefore, in the context of a civil engineering program in Chile, a novel approach combining problem‐based learning (PBL) with CFD was introduced into the curriculum of a fluid mechanics course to foster crucial competencies. This comprehensive methodology allows students to acquire fundamental theoretical knowledge that is directly related to specific problems in the classroom. Subsequently, students measure relevant variables in the laboratory, ultimately using these data to build computational models for comparing and contrasting reality with simulations. To gauge the effectiveness and impact of this PBL strategy, both quantitative analysis of student performance and qualitative analysis through surveys were conducted. The results reveal a significant improvement in student performance with the implementation of the PBL methodology, alongside a positive perception among students regarding its implementation. This underscores its benefits for learning, motivation, and academic performance. Additionally, the implementation of PBL was found to enhance both theoretical and practical understanding of concepts related to fluid dynamics and CFD simulation.